Akurasi petugas dalam penentuan sisa makanan pasien rawat inap menggunakan metode taksiran visual skala comstock 6 poin - Susyani Susyani; Endy Paryanto Prawirohartono; Toto Sudargo (Jurnal Gizi Klinik Indonesia, 2005)
Background: bserving plate waste is categorized as a simple way but yet still needs evaluation. When many foods are wasted, a dietitian should quickly respond and know the best way how to overcome the matters. There are three accurate ways to determine plate waste: plate waste weighing, visual estimation, and 24 hours recall. The application of each method really depends on its purposes. According to previous researches there are significant and positive correlations between the visual estimation of Comstock Scale and plate waste weighing. Visual estimation, moreover, has more advantages as it is easy to apply, cheap, and less time consuming. Considering those advantages, visual estimation needs to be socialized and considered as a new accurate method besides weighing methods.Objective: The objective of this study is to know the medical official accuracy in determining plate waste using visual estimation of 6 point Comstock Scale.Methods: An observational study was conducted using a cross-sectional design. Subjects were nurses and meal servants from hospital wards. Before the meal served to the patient the food is weighed, than the observers officer has to observed portion sized. After the patient having meal, plate waste should be estimated using Comstock Scale by the officer after that the plate waste have to be weight to know the actual weigh. The accuracy difference between two groups in determining plate waste using Comstock Scale were analysed with t-test.Results: There was significant differences of accuracy (p=0.01) between nurse group and meal servant in estimating wasted rice and wasted meat (p=0.02). The difference were not due to the job factor but the significant of various meal (p=0.0001). The work experience is a significant factor in the accuracy of plate waste (p=0.42). There was no correlation between kind of job and kind of meal (p=0.47), and kind of meal with the work experience (p=0.79).Conclusion: Visual estimation of 6 point Comstock scale could be used by both nurses and meal servant in determining plate waste.